An Occupational Perspective on Productive Aging among Older Adults: Occupational Therapy Implications. (2nd October 2022) - Empuerto, Cheyenne Chelsea; Afable, Aliza Marie; Bardos, Tristian Aura; Oñes, Gwinseth Kae; Soriano, Ezra Monique; Bulan, Paolo Miguel
Abstract: Aim: Productive aging is seen to have a positive influence on an individual's health and is vital in the quality of life for older adults. Occupational therapists promote productive aging both in the individual and community level, yet little is known about productive aging from older adults. With phenomenology, authors aimed to explain the phenomenon of productive aging through older adults' perspectives. Method: In-depth interviews were conducted on eight participants from a densely populated village in Cebu, Philippines. Results: Through thematic analysis, three themes emerged: (1) living life to its fullest as occupational beings, (2) physical and financial limitations as occupational limitations of aging, and (3) satisfaction with social responsibility as one's purpose. Conclusion: Collaborative efforts between occupational therapists and communities are needed to draft programs to provide older adults opportunities for socialization and volunteer and civic work. Communities are called to actively involve older adults in their activities.